Contribución al conocimiento de la reproducción y cuidado parental en Crotalus molossus nigrescens en el estado de Hidalgo, México - Fernández-Badillo, Leonardo; Torres-Angeles, Ferdinand (Instituto de Ecología, A.C., 2018)
The black-tailed rattlesnake (Crotalus molossus nigrescens) has a wide distribution in the Mexican territory. Nevertheless, field information about its reproductive biology is scarce, particularly in Hidalgo State. Here, we present the first report about clutch characteristics of Crotalus molossus nigrescens in Hidalgo State, and also about parental care behavior.